2022
DOI: 10.2196/34026
|View full text |Cite
|
Sign up to set email alerts
|

Ethical, Legal, and Social Implications of Symptom Checker Apps in Primary Health Care (CHECK.APP): Protocol for an Interdisciplinary Mixed Methods Study

Abstract: Background Symptom checker apps (SCAs) are accessible tools that provide early symptom assessment for users. The ethical, legal, and social implications of SCAs and their impact on the patient-physician relationship, the health care providers, and the health care system have sparsely been examined. This study protocol describes an approach to investigate the possible impacts and implications of SCAs on different levels of health care provision. It considers the perspectives of the users, nonusers, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Even though the themes of our scoping review touched upon the factors identified in established models of work-related perceived stress such as work content or work organization, we did not find any results concerning HCPs’ job satisfaction or perceived work-related stress explicitly with regard to SCs. Against this background, a subproject of the current research network CHECK.APP [ 33 ] focuses on this topic using a qualitative research approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the themes of our scoping review touched upon the factors identified in established models of work-related perceived stress such as work content or work organization, we did not find any results concerning HCPs’ job satisfaction or perceived work-related stress explicitly with regard to SCs. Against this background, a subproject of the current research network CHECK.APP [ 33 ] focuses on this topic using a qualitative research approach.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the analysis were discussed by the research team (EÖ, NR, CP, and MAR) to find an agreement for the final set of findings. The themes were then validated by 2 researchers (NR and CP), and methodological questions were discussed with a research partner from the research network CHECK.APP (AJW) [ 33 ], with which this work is associated but not funded.…”
Section: Methodsmentioning
confidence: 99%
“…This study is embedded in the larger context of the joint project "Ethical, Legal, and Social Implications of Symptom Checker Apps in Primary Health Care" (Acronym CHECK.APP) [42]. The CHECK.APP project is based on a mixed-methods design and has four foci (1: Ethical, legal, and social issues, 2: Epidemiology of SCA use and predictors of use, 3: Patterns of SCA use and impact on individuals, 4: Impact of SCA use on the health care system and health care workers).…”
Section: Study Design and Sampling Strategymentioning
confidence: 99%
“…As such, people increasingly turn to the internet for health information [41][42][43] and demand exists for health screening mobile apps to assist with condition diagnosis (e.g. check user symptoms against common condition symptoms) [44][45][46] .…”
Section: Introductionmentioning
confidence: 99%